2020
DOI: 10.21449/ijate.702041
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Academic Self-efficacy of Syrian Refugee Students: A Path Analysis Model

Abstract: In this study, the effect of resilience, perceived social support, life satisfaction and self-regulation variables on the academic self-efficacy of Syrian refugee undergraduate students were examined with a path analysis model. The sample consisted of Syrian undergraduate students living in Turkey. The sample of the research was randomly selected and participation was voluntarily. Data collection tools used were demographic information form, Arabic versions of academic self-efficacy, resilience, perceived soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Studies have illustrated that lower ASE is associated with poorer engagement and poorer academic performance when studying face to face [31] and online [32, 33]. Mental health has been shown to negatively impact on ASE, with individuals experiencing higher levels of stress and poorer social support having lower of levels of ASE [34, 35]. Given that those students who believe that they are not capable of completing certain academic tasks appear to have poorer academic outcomes, understanding the complete experience of students, and factors such as mental health that might hinder the development of their ASE is important.…”
Section: Academic Engagement and Self-efficacymentioning
confidence: 99%
“…Studies have illustrated that lower ASE is associated with poorer engagement and poorer academic performance when studying face to face [31] and online [32, 33]. Mental health has been shown to negatively impact on ASE, with individuals experiencing higher levels of stress and poorer social support having lower of levels of ASE [34, 35]. Given that those students who believe that they are not capable of completing certain academic tasks appear to have poorer academic outcomes, understanding the complete experience of students, and factors such as mental health that might hinder the development of their ASE is important.…”
Section: Academic Engagement and Self-efficacymentioning
confidence: 99%
“…An & Lee (2017) demonstrated that in the context of career exploration, career decision efficacy acted as a mediator between perceived career barriers/social support and career exploration behavior, suggesting that enhancing career decision efficacy could ameliorate the impact of perceived barriers and bolster career exploration efforts (An & Lee, 2017). Moreover, Sari et al (2020) found that in Syrian refugee students, selfregulation and perceived social support directly impacted academic self-efficacy, with life satisfaction serving as a mediator in the effect of perceived social support on academic outcomes (Sari et al, 2020). These findings illuminate the multifaceted ways in which self-efficacy and perceived social support interact with other psychological constructs to influence a wide range of outcomes, from career decision-making to academic engagement.…”
Section: Introductionmentioning
confidence: 97%